Bone implant materials from eegshell waste - Sopyan, Iis (Trans Tech Publications Ltd., Switzerland, 2015)
Hydroxyapatite powder has been synthesized from eggshell waste using a simple hydrothermal synthesis. The process involved drying and thermal decomposition of eggshell into calcium oxide followed by a hydrothermal reaction at a temperature of as low as 90C with ammonium di-hydrogen phosphate and water. The produced hydroxyapatite powder is extraordinarily fine with nanosize primary particles. The yield of conversion is high, ca. 90%. Hydroxyapatite pure phase can be maintained until calcination of below 900C, at which -tricalcium phosphate phase started to appear to transform into biphasic calcium phosphate. Its high purity as proved by XRD shown that the product fulfills medical requirement. The present invention provides an environmentally beneficial and straightforward method of producing hydroxyapatite for bone implant materials using eggshell waste.